2016
DOI: 10.1111/dgd.12271
|View full text |Cite
|
Sign up to set email alerts
|

Embryos aggregation improves development and imprinting gene expression in mouse parthenogenesis

Abstract: Mouse parthenogenetic embryonic stem cells (PgESCs) could be applied to study imprinting genes and are used in cell therapy. Our previous study found that stem cells established by aggregation of two parthenogenetic embryos at 8-cell stage (named as a 2 PgESCs) had a higher efficiency than that of PgESCs, and the paternal expressed imprinting genes were observably upregulated. Therefore, we propose that increasing the number of parthenogenetic embryos in aggregation may improve the development of parthenogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…For instance, a shRNA against H19 reduces its expression level while promoting cardiomyogenesis in Pg‐ESCs . Embryo aggregation also greatly improves the fidelity of imprinted gene expression of Pg‐ESCs .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a shRNA against H19 reduces its expression level while promoting cardiomyogenesis in Pg‐ESCs . Embryo aggregation also greatly improves the fidelity of imprinted gene expression of Pg‐ESCs .…”
Section: Discussionmentioning
confidence: 99%
“…Intracytoplasmic sperm injection (ICSI) was carried out by a piezo-driven unit using methods described elsewhere (Bai et al ., 2017), except that our experiment was performed in HEPES-CZB containing 5 μg/ml cytochalasin B (Sigma, C6762) at room temperature. Only the sperm head was injected into the oocyte.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmids used were as followed: psp73-KDM6A and GFP-C1-KDM6A were cloned from the cDNA of mouse ES cell line that established in our laboratory (Bai et al ., 2016). The antibodies covered were as followed: monoclonal anti-B23 antibody (Sigma, FC82291), monoclonal anti-UBF antibody (Sigma, WH00007343M1), polyclonal rabbit anti-H3K27me3 (Millipore, 07-449), monoclonal rabbit anti-PARP1 (Abcam, ab32138), monoclonal mouse anti-GAPDH (CW0266A, CWBiotech).…”
Section: Methodsmentioning
confidence: 99%
“…One of the first identified lncRNAs, H19, plays a wide range of roles in vivo . H19 can function as both a tumor suppressor or oncogene and also as a regulator of growth and development in multiple mammalian embryo tissues (Bai et al, 2016; Yoshimura et al, 2018). A previous study revealed that H19 is up-regulated in AS and is related to AS progression (Pan, 2017), but the underlying regulation mechanism has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%